The HLA-G cycle provides for both NK tolerance and immunity at the maternal–fetal interface - Tilburgs, Tamara (Proc Natl Acad Sci U S A, 2015)
The interaction of noncytotoxic decidual natural killer cells (dNK) and extravillous trophoblasts (EVT) at the maternal–fetal interface was studied. Confocal microscopy revealed that many dNK interact with a single large EVT. Filamentous projections from EVT enriched in HLA-G were shown to contact dNK, and may represent the initial stage of synapse formation. As isolated, 2.5% of dNK contained surface HLA-G. However, surface HLA-G–negative dNK contained internalized HLA-G. Activation of dNK resulted in the disappearance of internalized HLA-G in parallel with restoration of cytotoxicity. Surface HLA-G was reacquired by incubation with EVT. This HLA-G cycle of trogocytosis, endocytosis, degradation, and finally reacquisition provides a transient and localized acquisition of new functional properties by dNK upon interaction with EVT. Interruption of the cycle by activation of dNK by cytokines and/or viral products serves to ensure the NK control of virus infection at the interface, and is illustrated here by the response of dNK to human cytomegalo virus (HCMV)-infected decidual stromal cells. Thus, the HLA-G cycle in dNK can provide both for NK tolerance and antiviral immunity.